Significant correlation between uric acid levels and flow-mediated dilatation in patients with masked hypertension. (August 2014) - Sincer, Isa; Kurtoglu, E.; Calıskan, M.; Akkaya, E.; Vuruskan, E.; Küçükosmanoglu, M.; Çoşkun, F. Yılmaz; Inci, M. F.; Zorlu, A.
Abstract Background: Serum uric acid (UA) level is associated with prognosis in cardiovascular disorders such as sustained hypertension, diabetes mellitus and chronic kidney diseases. Increased UA levels in sustained hypertension may reflect early renal vascular alterations. However, it remains unclear if serum UA is associated with endothelial dysfunction in masked hypertensive patients. Methods: A total of 100 individuals (57% men and 43% women; mean 45 ± 8 years) with masked hypertension were included in the present study. The clinical and laboratory data were collected. Endothelial function was estimated by flow-mediated dilatation (FMD) of the brachial artery and expressed as percentage change relative to baseline diameter. Results: Univariate regression analysis showed that the FMD was significantly negative correlated with uric acid (r = −0.300, p = 0.002), ambulatory 24-h systolic blood pressure (SBP) (r = −0.275, p = 0.008), hs-CRP (r = −0.222, p = 0.033) and diastolic aortic diameter (r = −0.243, p = 0.019). In multivariate linear regression analysis, only uric acid levels and ambulatory 24-h SBP were significantly associated with FMD. Conclusion: There was an independent correlation between UA and FMD, and a higher UA level was related to worse endothelial function which may contribute to hypertension and cardiovascular morbidity.